2020
DOI: 10.1111/aor.13878
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plasma volume status on mortality following left ventricular assist device implantation

Abstract: Worsening systemic congestion is often the central trigger of hospitalization in patients with heart failure. However, accurate assessment of congestion is challenging. The prognostic impact of systemic congestion following durable continuous‐flow left ventricular assist device (LVAD) implantation remains unknown. Consecutive patients who received durable continuous‐flow LVAD implantation between January 2014 and June 2017 and were followed for 1 year were included. The association of preoperative plasma volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The methodology to estimate the PVS by using the Hakim formula, as a surrogate of systemic congestion, was demonstrated and validated by previous studies [ 8 , 9 ]. Its prognostic impact was demonstrated in cohorts of patients with severe aortic stenosis [ 12 ], ischemic heart disease requiring coronary artery bypass surgery [ 13 ], and advanced heart failure requiring a durable left ventricular assist device [ 14 ]. Given the clinical conditions where quantifying systemic congestion was observed to be feasible, we sought to estimate a comprehensive congestion profile in a cohort with a low likelihood of clinical congestion in addition to those who have a higher likelihood of a clinically abnormal congestion profile.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology to estimate the PVS by using the Hakim formula, as a surrogate of systemic congestion, was demonstrated and validated by previous studies [ 8 , 9 ]. Its prognostic impact was demonstrated in cohorts of patients with severe aortic stenosis [ 12 ], ischemic heart disease requiring coronary artery bypass surgery [ 13 ], and advanced heart failure requiring a durable left ventricular assist device [ 14 ]. Given the clinical conditions where quantifying systemic congestion was observed to be feasible, we sought to estimate a comprehensive congestion profile in a cohort with a low likelihood of clinical congestion in addition to those who have a higher likelihood of a clinically abnormal congestion profile.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of 3414 patients with heart failure with preserved ejection fraction, higher calculated estimates of PVS were independently associated with an elevated risk of long-term clinical outcomes, and particularly, heart failure hospitalization [ 20 ]. In an analysis of 186 patients who received a continuous-flow left ventricular assist device, high PVS was associated with higher mortality during follow-up [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tamaki et al followed a group of patients admitted for acute decompensated heart failure and found that the plasma volume status correlated with overall mortality and rehospitalization for decompensated heart failure, findings similar to those of Yoshihisa et al (27,28). The value of PVS for risk stratification has been examined for a range of other applications, including left ventricular assist device (LVAD) recipients, coronary artery bypass grafting (CABG) or acute respiratory distress syndrome (ARDS) (29)(30)(31). Several studies have also looked at the potential of PVS for outcome and mortality prediction in patients undergoing interventions for valvular disease.…”
Section: Introductionmentioning
confidence: 89%